Influence of transfer of creative information on the performance of football players - Duda, H.; Kaczor, M. (Journal of Kinesiology and Exercise Sciences, 2017)
The increasing level of sporting achievements is the reason for seeking new and different solutions in different areas of the training process. It is therefore aimed at enriching training content with new methods, forms or introducing a more effective organization of training classes. It should be assumed that the way to improve the effectiveness of training consists in combining developmental activities: motor skills, special motor abilities and mental abilities (Naglak 2010, Duda 2016). Among these athletic qualities, considerable reserves are recognized in the teaching-learning of special motor activities and tactics in which athlete's mental abilities are utilized. Hence, by looking for new ways to optimize the training process for players, attention is drawn to a problem that until recently was unpopular in sports learning, and whose relevance is systematically increasing, ie the need for intellectualization of the training process. The aim of the research Demonstrating the influence of conscious analysis of the movement task among football players on their performance and on the basis of the importance of thought processes for the efficient performance of movement tasks determining directions for creative teaching of the sport game as an effective way of teaching technical and tactical activities. Material and methods of testing The test group will be football players in three age categories: • Footballers (U-12) • Juniors (U-16) • Seniors In the research process, the creative method will be applied to the creative exercises (Bergier 1996, Duda 2016) based on a conscious analysis of the motor activity. Results: The analysis of the research results shows that creative teaching learners achieve better results in motion Conclusions: 1. Efficacy of motor activity requires understanding of causal relationships. 2. Mentalization of the training process increases the effectiveness of the movement of players.